Power of Hypoperfusion in Predicting Recurrent Transient Ischemic Attacks: Protocol of a Prospective Cohort Study - Wang, Yue; Liang, Huazheng; Jin, Lingjing; Wang, Shaoshi (Frontiers in Human Neuroscience, 2021)
Background: Transient ischemic attack (TIA) has a high incidence of recurrent vascular events. Hypoperfusion is one of the factors that are closely correlated with 7-day recurrence of TIA. This study aimed to evaluate the power of hypoperfusion shown on magnetic resonance (MR) perfusion imaging in predicting the incidence of 7-day recurrence of ischemic events after TIA. Methods/Design: REATTACK is a prospective multi-centered cohort study on the correlation between MR perfusion and TIA recurrence. Ninety patients aged ≥18 years with recent (<7 days after onset) clinical TIA will be continuously included. All the patients will undergo diffusion-weighted imaging (DWI) and perfusion-weighted imaging (PWI) assessments within 24 h after the onset of TIA. The subjects will then be divided into a PWI positive group and a PWI negative group according to the time-to-maximum of the residue function (Tmax). PWI will be repeated after 7 days and in 3 months. The primary clinical outcome will be the recurrence of TIA within 7 days after the onset of TIA. Secondary outcomes will be the recurrence of TIA in 3 months and modified Rankin scale (mRS) score. A chi-square test will be performed to compare the difference in the incidence of recurrent TIA between the two groups, and rank sum test in the mRS score. Multivariate logistic regression will be simultaneously performed to analyze the risk factors for the recurrence of TIA. Discussion: The results of this study will confirm whether abnormal Tmax helps to identify the patients with TIA who have high risks of recurrent ischemic events. This would largely improve the prognosis of patients with TIA. Trial Registration:www.chictr.org.cn, registration number: ChiCTR2000031863, registered on 12 April 2020.